Biochemical activity of plants of the genus Alternanthera after UV-C radiation exposure - Braga, Eugenia Jacira Bolacel; Klein, Fátima Rosane Schuquel; Reis, Andressa; Kleinowski, Alitcia Moraes; Einhardt, Andersom Milech; Deuner, Sidnei; Amarante, Luciano; Peters, José Antonio (Revista Brasileira de Biociências, 2018)
UV-C radiation interferes with the physiological processes of plants. The increment of secondary metabolites, such as flavonoids and betalains as well as enzymatic activities, can explain the behavior of plants exposed to radiation. The objective of this study was to analyze the possible changes in the metabolism of plants of Alternanthera sessilis, Alternanthera brasiliana and Alternanthera philoxeroides, when exposed to different periods of UV-C radiation. Plants from in vitro culture were acclimatized in greenhouse for 60 days before they were exposed to UV-C radiation for 0, 5, 10, 15 and 20 minutes. Biochemical analyses of production of total betanidin, betanin, betaxanthins, flavonoids and the response of antioxidant enzymes as a result of exposure to UV-C radiation were carried out at the end of this study. The results showed that there was an increment of these secondary metabolism compounds in the species A. sessilis, and the maximum values were achieved after 10 and 12 minutes of exposure. The species A. brasiliana showed increased betanin content after 16 minutes of exposure. For the enzyme superoxide dismutase (SOD) there was no significant difference among the species in the different periods of exposure, for catalase (CAT), the species A. philoxeroides showed greater activity, differing significantly from the other species. Greater activity of ascorbate peroxidase (APX), for this species, at 20 minutes of UV-C radiation exposure was also found. Malondialdehyde (MDA) content increased in A. philoxeroides and A. sessilis,   because of UV-C radiation. It follows that the species studied trigger different protection mechanisms in the face of UV-C radiation